The influence of servant leadership on shared leadership development in Sport for Development - Svensson, Per G; Jones, Gareth J; Kang, Seungmin (Journal of sport for development, 2021)
Leadership is critical to the success of sport for development (SFD) organizations that operate in environments characterized by limited resources, growing competition, and blurred institutional boundaries. Previous research has primarily explored the efficacy of different leadership styles within SFD contexts and examined how leadership contributes to key dimensions of organizational capacity, performance, and other related concepts. Servant leadership and shared leadership have emerged as two particularly viable frameworks, yet there remains limited knowledge of how these approaches are developed and related in SFD. The current study is based on surveys from 100 employees of SFD organizations and utilized regression analysis to examine the relationship between salient organizational factors, servant leadership, and shared leadership. Results indicate that after controlling for salient organizational factors, servant leadership explains a significant portion of the variance in shared leadership. The discussion focuses on the theoretical and practical implications of these findings and highlights key areas for future research.